Assessing the oral bioavailability of difluorosialic acid prodrugs, potent viral neuraminidase inhibitors, using a snapshot PK screening assay. Issue 12 (15th June 2015) - Arns, Steve; Tan, Jason; Sun, Sharon; Galey, Adam; Zisman, Natalia; Ross, Fiona; Udechukwu, Jenna; Dercho, Samantha; Gusti, Vionarica; Paquette, Jay; Webb, Murray; Bourque, Elyse; et al.
Graphical abstract: Abstract: Difluorosialic acids (DFSAs) are potent inhibitors of viral neuraminidase that demonstrate activity against oseltamivir- and zanamivir-resistant strains of influenza. Unfortunately, low oral bioavailability precludes their development as second generation neuraminidase inhibitors for treating influenza as this leaves them unsuitable for use in an oral formulation. Herein is described the preparation of a series of DFSA prodrugs designed to increase oral bioavailability. These prodrugs were evaluated using a snapshot PK screen and stability tests, with successful candidates being further assessed with a full pharmacokinetic workup. These new prodrugs increased oral bioavailability by up to three times that seen for the parent DFSAs.